The Effect of Government Spending on Economic Growth in the Sultanate of Oman (International Journal of Financial, Administrative and Economic Sciences, 2024)
Understanding the relationship between government spending and economic growth is crucial because it is complex. While well-directed investments create a more favorable environment for businesses to thrive and thus stimulate economic growth, excessive spending may lead to inflation and crowd out the private sector, accordingly, hindering growth. This study seeks to determine the effect of public expenditures (investment expenditures, current expenditures, contributions, and other expenditures) on the Sultanate of Oman's economic growth, using quarterly data from 2010 to 2022. The study relies on the descriptive approach and the analytical quantitative approach by forming and estimating a standard model and then testing it using the bounds test of the Autoregressive Regression of Distributed Lags (ARDL) methodology to determine the long-term and short-term effects of public expenditures on economic growth through EViews 13. The results of the analysis show that there is a long-term and short-term effect of government investment expenditures on economic growth in Oman during the study period. The results also indicate that there is no significant effect of current government expenditures, contributions, and other government expenditures, neither in the short term nor in the long term. The study recommends a set of recommendations for decision-makers in Oman, the most important of which is to focus on investment expenditures, especially infrastructure projects that improve productivity, innovation, productive capacity, and long-term competitiveness.
Keywords: Sultanate of Oman; Government Spending; Economic Growth; Autoregressive Distributed Lag (ARDL) Model